A Global Overview of Restorative Shellfish Mariculture - Carranza, Alvar; zu Ermgassen, Philine S. E. (Frontiers in Marine Science, 2020)
Farming of marine organisms (mariculture) represented 36% of global aquaculture, with molluscs representing 58.8% in live weight. Mollusc populations in some locations are, however, threatened by degradation of the ecosystems and/or over-fishing. This threat is increasingly being addressed through Restorative Shellfish Mariculture (RSM), as opposed to mariculture alone. There is no general consensus in the literature on what can and cannot be considered RSM. While maximization of benefits other than provisioning services is often considered a prerequisite, in other cases the maximization of fisheries yields is prioritised. Here we define RSM as the farming of marine shellfish, implying some form of intervention during the species life cycle, in order to address negative socio-ecological issues arising from the unsustainable use of marine ecosystems, independent of the final ownership regime of the resource. Strategies for developing RSM were reviewed and classified along a gradient from the most conservation-oriented (e.g. habitat restoration, reintroduction of locally extinct endangered species), to the most fisheries-oriented (including some forms of fisheries enhancement), and classified as Non-hatchery Dependent or Hatchery Dependent strategies. We reviewed the targeted species and strategies implemented across 584 individual projects developed in the last decades in North America, Europe, Asia, Oceania and South America. We found that some 48 species, including 34 bivalves and 15 gastropods were targets of RSM in 34 countries. US projects accounted for ca. three quarters of the total (N=438), with Philippines, Japan and Australia also being home to a large number. More than 90% of the projects involved five species, namely the eastern oyster (Crassostrea virginica, N=379), the giant clam (Tridacna gigas, N=65), the Olympia oyster (Ostrea lurida, N=25), the bay scallop (Argopecten irradians, N=25) and the hard clam (Mercenaria mercenaria,N=15). Of the RSM projects, 51% used Non-hatchery dependent methods, mostly habitat restoration providing substrata for settlement, whilesome 49% involved hatcheries. Some three percent of the projects combined both methods. This review provides an overview of the breadth and depth and aims of RSM globally, develops a broad definition of the activity, and proposes a structure for classifying RSM.